How GPUs Work. - Luebke, David; Humphreys, Greg (Computer (00189162), 2007)
The article discusses the technological advances in graphics processing units (GPU). The author attributes the advances to consumer demand for video games, advances in manufacturing technology, and the exploitation of the inherent parallelism in the feed-forward graphics pipeline. Presently the raw computational power of a GPU is comparatively larger than the most powerful central processing unit (CPU). Also, GPUs can implement many parallel algorithms directly using graphics hardware, which the text suggests can often help achieve tremendous speed increases. The operational procedures of GPUs are included in the text.